Dakwah Kepada Golongan Profesional di Pahang: Da`wah to the Professional Group in Pahang - Mokhtar, Ahmad Effat; Hashim, Ibrahim; Jemali, Misnan; Ismail, Abdul Munir (Perspektif Jurnal Sains Sosial dan Kemanusiaan, 2017)
This article discusses da`wah to the professional group in Pahang. The issues studied are the coming of Islam in Pahang, the methodology of da`wah programme organised by da`wah bodies to the professional group in Pahang such as Pahang Department of Islamic Religion, Muslim Youth Movement of Malaysia and Organization of IKRAM. This study employs the library research and field research methods by using interviews. Therefore, in facing da`wah challenges nowadays, preachers have to vary the methodologies of da`wah to attract the society to Islam especially the professional group. The findings generally show that the participation of professional group in da`wah programme is still low because they are busy with their profession and the da`wah approach used to this group is less appropriate.